A SURVEY OF ERRORS INVOLVING JAPANESE TRANSITIVE AND INTRANSITIVE VERBS AMONG INTERMEDIATE VIETNAMESE LEARNERS - IMPLICATIONS FOR EFFECTIVE TEACHING METHODS - Phuong, Tran Thi Minh (VNU Journal of Foreign Studies; Vol 36 No 5DO - 10.25073/2525-2445/vnufs.4612, 2020)
This study investigates the use of Japanese intransitive and transitive verbs among the Vietnamese using KY Corpus. It identifies major features of errors committed by the Vietnamese in their use of Japanese intransitive and transitive verbs, namely (1) errors due to confusion of verb transformation, which account for a high proportion; (2) errors because of the Vietnamese learners' failure in recognizing perspectives that result in construal of the real world, which may rely on the speakers' own perspective or on that of the perceived entities; (3) errors resulting from negative transfer or word-for-word translation from L1 to L2 involving the passive voice, causative constructions; and (4) errors related to the use of auxiliaries in sentences with intransitive and transitive verbs.